Characterization of anion exchange fiber for simultaneous removaof Cr(VI) and as(V) in mineral processing wastewater - Lee, Seung Chan; Kang, Jin Kyu; Choi, Nag Choul; Lee, Chang Gu; Kim, Song Bae (Desalination and Water Treatment, 2018)
In this study, a modacrylic anion exchange fiber (KaracaronTM SA2) made from acrylonitrile and vinyl chloride was used for the removal of Cr(VI) and As(V) in aqueous solutions. This study focused on the two parts: (i) investigate the simultaneous removal of Cr(VI) and As(V) present in mineral processing wastewater by the SA2, and (ii) examine the protonated amine sites available on the SA2 in response to pH change using X-ray photo electron spectroscopy (XPS) analysis. Batch experiments indicated that the maximum removal capacities for Cr(VI) and As(V) were 2.350 and 0.346 mmol/g, respectively. The SA2 was successfully regenerated by 0.1 M NaCl solution and reused for five adsorption-desorption experiments. The removal of Cr(VI) and As(V) was influenced by the solution pH. The pH dependency of Cr(VI) and As(V) removal was closely related to both the number of protonated amines available for anion exchange and speciation of Cr(VI) and As(V) in response to the pH change. XPS analysis demonstrated that the C-N+ peak (401.5 eV) was prominent at pH 2. As pH increased to 4 and 10, the C-N+ peak gradually decreased due to partial deprotonation of the anion exchange sites. At pH 12, the C-N+ peak disappeared because nearly all of the exchange sites were deprotonated. Simultaneous removal experiments in mineral processing wastewater (pH = 2.9; Cr(VI) concentration = 60.2 mmol/L; As(V) concentration = 67.5 mmol/L) demonstrated that Cr(VI) removal by the SA2 tended to be greater than that of As(V). The Cr(VI) and As(V) removal capacities in the wastewater were 1.587–3.098 and 0.042–2.124 mmol/g, respectively, at fiber dosages of 2–20 g/L.
Keywords: Anion exchange fiber; Arsenate; Chromate; Ion exchange; Mineral processing wastewate